POTENSI JENIS-JENIS IKAN AIR TAWAR KONSUMSI MASYARAKAT ALIRAN SUNGAI DIGOEL, KABUPATEN BOVEN DIGOEL, PAPUA, DAN BEBERAPA LANGKAH PENGELOLAANNYA - Rarung, Lexy K; Pratasik, Silvester B (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2010)
This study aimed at providing information on freshwater fish living in Digoel River, Boven Digoel Regency, Papua, edible for local people and some management options. Data were collected from observing the fishing activities and Tanah MerahÂ  market, and through personal interviews as well. Results showed that there were about 23 species of native and introduced fish living in the Digoel River. Native fish population is decreasing as a result of forest clear cut, pollution, irrational fishing and predation. Therefore, management actions should be taken.